EFISIENSI USAHA AYAM RAS PETELUR DI DESA TAMAN KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Phaulinus Wera Vera; Cening Kardi; Fajar Kartika Lestari, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Laying hens are chickens raised specifically for their eggs. Indonesian native chickens generally come from wild jungle fowl and ducks, which are caught and reared for their eggs. The livestock sector has a very important role in meeting the needs of animal protein. The research objectives were: to analyze the production function of laying hens in Taman Village, Abiansemal District, Badung Regency and to analyze the allocative efficiency of the use of production factors in laying hens business in Taman Village, Abiansemal District, Badung Regency. The research was conducted through a survey of 18 breeders. The results of this study indicate that: Production factors that have no significant effect: the general population, gold coin 105 c feed, letoenic strain vaccines and vitralit vaccines. While those that have a real effect: gold coin 104 c feed, egg stimulant vaccines and labor.Efficiency in the use of production factors in laying hens business in Taman village, namely: factors of production that are not yet efficient: feed 1 (gold coin 104 c), vaccine 1 (letonic strain), vaccine 2 (egg stimulant) and labour. vaccine 3 (vitralit) has been efficient. While the production factors are not efficient: the number of chickens and feed 2 (gold coin 105 c).